Physico-Chemical and Thermodynamic Studies Associated with Micellization of Sodium Dodecyl Sulfate in n-Alkanol/Water Mixtures - Rafati, A.A.; Safarpour, M. (Asian Journal of Chemistry, 2010)
Conductometric technique has been used to investigate the equilibrium properties of sodium dodecyl sulfate in the presence of a series of aliphatic alcohols. The influence of medium chain alcohols on the micellization behaviour of sodium dodecyl sulfate is investigated and it is shown that the critical micelle concentration and degree of micellar dissociation (α) increase upon addition of alcohols, depending on the chain length of alcohols. The thermodynamic functions for the micellization were calculated at various conditions. The results showed that the presence of alcohols decreases the tendency for micelle formation. The addition of alcohols is considered to affect the micellar stability by changing the composition and dielectric constant of the environment.